2012
DOI: 10.1159/000335251
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization Effect of Preseasonal Seven-Injection Allergoid Immunotherapy with Olive Pollen on Basophil Activation: The Efficacy of Olive Pollen-Specific Preseasonal Allergoid Immunotherapy on Basophils

Abstract: Background: It has previously been demonstrated that subcutaneous immunotherapy with allergoids positively affects clinical and immunological parameters even after 7 preseasonal injections. However, its effect on basophil activation remains unclear. We investigated the effect of preseasonal allergoid immunotherapy on basophils and concomitantly assessed its clinical and immunological efficacy in olive pollen-monosensitized patients. Methods: This study enrolled 437 consecutive patients with respiratory allergy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
(27 reference statements)
2
24
0
2
Order By: Relevance
“…However, there are several studies showing the increment of specific IgG antibodies by allergoid immunotherapy [22,26,27]. As shown in our study, the suppressive effect of the therapy on basophil activation at the end of treatment and at the peak of the grass pollen season after treatment further supports the powerful immunogenicity of allergoids.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, there are several studies showing the increment of specific IgG antibodies by allergoid immunotherapy [22,26,27]. As shown in our study, the suppressive effect of the therapy on basophil activation at the end of treatment and at the peak of the grass pollen season after treatment further supports the powerful immunogenicity of allergoids.…”
Section: Discussionsupporting
confidence: 81%
“…However, we did not evaluate basophil activation beyond the first grass pollen season after treatment. There was a finding of a sustained decrease of basophil activation compared to baseline after 8 months of short-term, preseasonal, olive pollen allergoid immunotherapy in 1 uncontrolled study [22], but some studies have not demonstrated a change in basophil activation with immunotherapy [23,24]. A placebo-controlled trial with five-grass pollen sublingual immunotherapy did not find any alteration in allergen-induced basophil CD203c expression after 4 months of treatment, despite a symptomatic improvement of the subjects' rhinoconjunctivitis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover a decrease in the number of mast cells and basophils, determined by the SPT and the basophil activation test (BAT), respectively, has been observed in immunotherapy for aeroallergens (Gokmen et al 2012;Plewako et al 2006). Similarly, in food allergies treated with OIT protocols for milk, egg, and peanut, decreases in the serum levels of sIgE, SPTs, BATs and increase of allergen-specific IgG4 after 3-6 months of treatment have been reported (Table 2).…”
Section: Mechanisms Of Oit In Food Allergymentioning
confidence: 88%
“…Akım sitometrik bazofil aktivasyon testinin allerjen immünoterapisinin etkinliğini izlemede de kullanıldığını gösteren klinik çalışmalar vardır (34)(35)(36). Örneğin, venom immünoterapisi, Betula ve zeytin poleni immü-noterapisinin klinik etkinliğini semptom skorları yanı sıra bazofil aktivasyon testi ile gösteren çalışmalar literatürde mevcuttur (Şekil 11).…”
Section: Allerjen İmmünoterapisinin Takibi Ve Tedavinin Etkinliğini öunclassified